In vitro measurement of myocardial impedivity anisotropy with a miniature rectangular tube - Tsai, Jang Zern; Will, James A.; Vorperian, Vicken R.; Hubbard-Van Stelle, Scott; Cao, Hong; Tungjitkusolmun, Supan; Choy, Young Bin; Webster, John G. (My University, 2003)
Due to rapid change of fiber orientation, it is difficult to measure myocardial impedivity separately in a longitudinal or transverse fiber direction without mutual influence in the two directions. Previously published values of the longitudinal and the transverse myocardial impedivity were derived indirectly from measurements that mixed the impedivity in all directions. Those values are questionable because the derivations were based on a simplified uniform myocardial fiber model. In this paper, a miniature rectangular tube was devised to facilitate direct measurement of myocardial impedivity in a uniform fiber direction. The average transverse-to-longitudinal ratio of the measured in vitro swine myocardial impedivity was about 1.66 from 1 Hz to 1 kHz and dropped to 1.25 at 1 MHz. The result is important for accurate modeling of the electrical property of myocardium in biomedical research of radio-frequency cardiac catheter ablation.
Keywords: Anisotropy; Four-terminal impedivity; Myocardial impedivity; Resistivity